The Place of Publishing in the Activities of Old Diaspora Entrepreneurs Engaged in Financial Services: The Case of Jonas M. Tananevičius - Misiūnas, Remigijus (Knygotyra, 2025)
Jonas Mykolas Tananevičius was one of the most prominent publishers and businesspeople of the old Lithuanian diaspora at the beginning of the 20th century. Having acquired the newspaper Katalikas and financial services businesses from Father M. Kriaučiūnas in 1901, J. M. Tananevičius further developed them for several years, while also founding a private bank. During that time, he became one of the largest diaspora businesspeople well beyond the scope of the City of Chicago. Only A. Olšauskas, the publisher of the newspaper Lietuva, who also controlled a bank and developed several businesses related to financial intermediation, could perhaps be comparable with him. Publishing constituted an important part of the business run by J. M. Tananevičius; his newspaper Katalikas was the first in the diaspora to become a daily, and, among the approximately 90 books he published, many were not only commercially successful but also culturally significant. J. M. Tananevičius was also active in the public life of the expatriate community. However, the bankruptcy of the Katalikas bank in 1916, followed by a trial of J. M. Tananevičius in 1917, revealed another side of his business. It became clear that, for many years, his business had been managed dishonestly; J. M. Tananevičius and his relatives had embezzled the depositors’ money and thus enhanced their own quality of life. Despite such an ending, J. M. Tananevičius remains a striking figure of the old diaspora, worthy of attention from researchers of diaspora and publishing history.